Ageing, the digital and everyday life during and since the Covid-19 pandemic - Martin, Wendy; Collett, George; Bell, Chris; Prescott, Amy (Frontiers in Psychology, 2023)
Introduction: During and since the Covid-19 pandemic there has been an intensified integration of digital technologies into the everyday lives of older people.. We do, however, know little about the ways in which older people incorporate digital technologies and communications into their daily lives and their own meanings, embodiment and experiences of the digital during and since the Covid-19 pandemic Method: The aim of our research was to explore the use of digital devices during and since the Covid-19 pandemic and to identify facilitators and barriers to incorporating digital devices into everyday life. The research involved a series of online focus groups with people aged between 63 and 86 years living in the United Kingdom and were conducted in 2022. Each focus group lasted around 90 minutes and data was audio-recorded and transcribed. The data was analysed thematically.Results: From the analysis, three interconnecting whilst analytically distinct themes around the meaning and experiences of using digital devices in everyday life during and since the pandemic, are thematically presented as: (1) Incorporating the digital into everyday life; (2) Social and digital connectivity; and (3) Challenges and limitations of the digital in everyday life.The research has provided insights into the way digital devices were used by older people during and since the Covid-19 pandemic. In particular, we highlight the increasing importance of digital connectivity and the ways in which older people actively engage (and resist) technologies of communication in their daily lives; and the significance of embodied co-presence and the immediacy of shared space and/or time is highlighted.